Peran Orang Tua dalam Menumbuhkan Sikap Kemandirian Belajar Anak-Anak Pemulung - Ismiati; Surya Hadi Darma; Dyah Wulandari (Paedagogie: Jurnal Pendidikan dan studi Islam, 2023)
Abstract   The role of parents is an important component in shaping the child's personality, especially in the behavior and independence of children's learning. The daily habits and attitudes of parents are always seen, assessed and imitated by children. The purpose of this study was to determine the role of scavenger parents in fostering learning independence in their children, what factors are supporting and inhibiting factors in growing the independence of scavenger children in Ciseureuh Village, Purwakarta District, Purwakarta Regency. This study uses the theory of Suhendri & Mardalena which states that the characteristics of children who are independent in learning are that children's learning activities do not depend on other people, teachers, friends and even parents. This study uses a qualitative method, which describes the role of scavenger parents in fostering children's learning independence. In collecting data using observation, interviews and documentation as well as triangulation, while the process of analyzing data using the theory of the Miles and Hubermen model which includes, data reduction, data presentation and verification or examination of conclusions. The results of this study showthat the role of parents of scavengers in RT.10/RW07, Ciseureuh sub-district, Purwakarta district in fostering an attitude of learning independence is quite well realized. obligations of children independently from an early age. As for children's learning independence, it can be seen from the learning independence of children who diligently attend school every day, do assignments without being asked or forced and some children get achievements in school, find their own money to buy quotas when learning online by scavenging or busking and even become parking attendants. Supporting factors in growing the independence of scavenger children in RT. 10/RW07, Ciseureuh sub-district, Purwakarta district, can be seen from the internal and external factors that are well fulfilled. While the inhibiting factors are caused by parents not understanding proper parenting, giving excessive freedom, not being a good role model and not giving rewards when their children get achievements.